Control and evaluation of room interior lighting using digital camera as the sensor - G Varghese, Susan; Pearl Kurian, Ciji; I. George, V; S. Sudheer Kumar, T (International Journal of Engineering and Technology, 2018)
This paper reports the results of measurements performed in a test room to test how digital camera can be used as luminance meter and thus to investigate the lighting control scheme based on the inputs coming from camera. An indoor lighting control scheme which adapts according to the daylight availability is presented in this work. The camera calibration procedure based on High Dynamic Range Imaging technique is used to obtain the camera response function which allows to relate pixel values obtained from the image and the photopic luminance values. Luminance gradient evaluation for the uniformity analysis is discussed for the test room.Â Â